Pengaruh Beberapa Jenis Lampu terhadap Hasil Tanaman Selada Keriting Hijau (Lactuca sativa L.) pada Plant Factory - Rusmita, Gst Ayu Putu Ika Yulia; Suada, I Ketut; Wirawan, I Gede Putu (Agrotrop : Journal on Agriculture Science, 2023)
Effect of Several Types of Lights on Yield of Green Curly Lettuce (Lactuca sativa L.) at Plant Factory. Light intensity is the most important factor in the process of plant growth, light sources that can be received by plants other than the sun can also use light. This research took place from March to April 2022. This research was conducted at the Plant Factory, Faculty of Agriculture, Jl. Moyo Island No. 16X, Pedungan, South Denpasar. In this research experiment the design used was a completely randomized design (CRD) with 6 types of lamp treatments, namely: LED grow light, white LED lamp, yellow fluorescent lamp, white fluorescent lamp, combination of white, yellow, far-red HPL lamps and white fluorescent lamps. HPL combination of red, blue, yellow and repeated 4 times. The results of statistical analysis showed that the type of lamp treatment had a very significant effect on all observed variables, except number of leaves, and root dry weight. The type of lamp treatment had an effect on the yield of lettuce grown at the plant factory and was indicated by the total fresh weight with a value of (171.50 g) and total dry weight with value of (5.09 g) which were significantly different from other treatments. The best type of lamp for lettuce growth and yield is the best yellow fluorescent lamp.